Pengembangan Aplikasi Manajemen Pra Lelang (Studi Kasus: PT Pertamina EP) - Fathania Fadilla; Hiwamat Aryadita; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In order to get a valid pre bidding document of prebidding process at PT Pertamina EP, procurement division held a pre bidding document inspection process. Procurement Division needs some information regarding to pre bidding document status and history. The one who proposed the document also need some information regarding to status of their document. This research is trying to fulfill their needs by providing a system that can simplify pre bidding inspection process. This system is built using CodeIgniter framework and Javascript for some additional features. Waterfall approach is chosen in order to get user's needs at the beginning of development process. This research begins with the study of literature in order to get deep understanding related to the research. The next step is Analysis of Business Process and System Requirements, System Planning System Implementation, and System Testing. Two as-is business processes, 2 to-be business processes, and 14 functional requirements is produced in order to get the concept of existing business processes, give the solution for the problem, and give the basic guideline for development process. The result of black box testing showed that Pre Bidding Management Application has run properly, because there's no error at the testing process. The result of User Acceptance Testing showed that Pre Bidding Management Application has fulfilled the user's needs, because the percentage of the total score from the user's response is greater than 50%.